JONATHAN EDWARDS’ ARGUMENT THAT GOD’S END IN CREATION MUST MANIFEST HIS SUPREME SELF-REGARD - Schultz, Walter J. (Jonathan Edwards studies, 2014)
In his dissertation Concerning the End for which God created the World Jonathan Edwards’ argumentation includes the claim that God’s end in creation must manifest God’s supreme regard for himself.Establishing this claim is required by Edwards’ stated goals in writing the dissertation. His constructive goal was to provide—on shared assumptions—a logically consistent account of Christianreligious experience as a "work" of God. His polemical goal was to refute contrary accounts. These accounts were influenced in part by British rational intuitionism. They served as the conceptualfoundations of what Edwards and others referred to as "fashionable schemes of divinity," which were being promoted by clerics in the New England colonies. Edwards’ opponents held that thereare "eternal and immutable" moral rules, that these are discerned by one’s natural faculty of reason, that the freedom of the will enables compliance with them, and that even God (somehow) encounters them and complies. So, God’s end in creation—whatever it is—will also be so informed and directed,fully subordinate to "reason’s dictates." Edwards argues that, since God is self-sufficient and creation is ex nihilo, nothing outside of God directs God or motivates God. In spite of the appearanceof inappropriate self-centeredness, only God can be God’s original ultimate end in creation.Therefore, while the end for which God created the world is God and—whatever form this end takes as something to be achieved by divine action—it will manifest God’s supreme regard for himself.